The Alma Survey of Gas Evolution of Protoplanetary Disks (Age-Pro). Ii. Dust and Gas Disk Properties in the Ophiuchus Star-Forming Region - Miley, J; Gonzalez-Ruilova, C (Institute of Physics, 2025)
The ALMA survey of Gas Evolution in PROtoplanetary disks (AGE-PRO) Large Program aims to trace the evolution of gas disk mass and size throughout the lifetime of protoplanetary disks by using the Atacama Large Millimeter/submillimeter Array (ALMA). This paper presents Band-6 ALMA observations of 10 embedded (Class I and Flat Spectrum) sources in the Ophiuchus molecular cloud, with spectral types ranging from M3 to K6 stars, which serve as the evolutionary starting point in the AGE-PRO sample. While we find four nearly edge-on disks (≥70°), and three highly inclined disks (≥60°) in our sample, we show that, as a population, embedded disks in Ophiuchus are not significantly contaminated by more-evolved, but highly inclined sources. We derived dust disk masses from the Band-6 continuum and estimated gas disk masses from the C18O J = 2−1 and C17O J = 2−1 lines. The mass estimates from the C17O line are slightly higher, suggesting C18O emission might be partially optically thick. While the 12CO and 13CO lines are severely contaminated by extended emission and self-absorption, the C18O and C17O lines are allowed to trace the radial extent of the gaseous disks. From these measurements, we found that the C18O J = 2−1 and C17O J = 2−1 fluxes correlate well with each other and with the continuum fluxes. Furthermore, the C18O and C17O lines present a larger radial extension than disk dust sizes by factors ranging from ∼1.5 to ∼2.5, as is found for Class II disks using the radial extension of the 12CO. In addition, we have detected outflows in three disks from 12CO observations. © 2025. The Author(s). Published by the American Astronomical Society.